Comparative Analysis of the Competences of Gymnasium Students in Lower Silesia Districts - Błaczkowska, Anna; Grześkowiak, Alicja; Król, Anna; Stanimir, Agnieszka (Analiza porównawcza umiejętności gimnazjalistów w powiatach dolnośląskich, 2011)
The paper presents the analysis of students’ scores in compulsory examination administered in the last grade of the gymnasium. The conducted multivariate analyses allowed to determine spatial diversity and dynamics of the competences of students in the lower secondary level of education in Lower Silesia districts between 2002 and 2010. The following alarming conclusions are the result of this research: in most districts the gymnasium students are prepared for further stages of education and for applying the knowledge and skills in life only to a medium or weak degree; the number of districts in which the gymnasium students obtained good and very good results decreased in 2010; number of points scored in the competence areas where creativity and constructive thinking was significantly decreased.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 76-87
Keywords: ewaluacja; edukacja; szkolnictwo ponadpodstawowe; evaluation; education; primary education